Dissociation of the anti-hapten and anti-carrier responses of mice injected with dinitrophenylated lipopolysaccharide. - Von Eschen, K B (1981)
The quantitative and qualitative nature of the antibody responses of euthymic (normal, RML) and athymic (nude) mice injected with dinitrophenylated (DNP) lipopolysaccharide (LPS) was evaluated. Antibody responses to both the haptenic (DNP) and carrier (LPS) determinants were measured. On a quantitative basis, RML and nude mice stimulated with DNP-LPS produced only primary anti-DNP responses, whereas both primary and secondary anti-LPS responses were elicited by this conjugate. The failure of DNP-LPS to trigger secondary anti-DNP responses was not dependent on the amount of DNP-LPS given in the primary or secondary doses and could not be overcome by repeated injections of DNP-LPS. Also, the anti-DNP responses of RML mice injected repeatedly with DNP-LPS were restricted to immunoglobulin M antibodies whereas both immunoglobulin M and G anti-LPS responses were elicited. Nude mice also produced immunoglobulin G antibodies to the LPS determinants. These data showed a dissociation of the anti-hapten and anti-carrier antibody responses and suggested that different immunological signals were functioning in the respective anti-DNP and anti-LPS responses.